2017
DOI: 10.3389/fnana.2017.00032
|View full text |Cite
|
Sign up to set email alerts
|

The Olfactory System Revealed: Non-Invasive Mapping by using Constrained Spherical Deconvolution Tractography in Healthy Humans

Abstract: Although the olfactory sense has always been considered with less interest than the visual, auditive or somatic senses, it does plays a major role in our ordinary life, with important implication in dangerous situations or in social and emotional behaviors. Traditional Diffusion Tensor signal model and related tractography have been used in the past years to reconstruct the cranial nerves, including the olfactory nerve (ON). However, no supplementary information with regard to the pathways of the olfactory net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 112 publications
1
30
0
Order By: Relevance
“…More recently, we used constrained spherical deconvolution (CSD)‐based tractography, a diffusion MRI‐based technique allowing in vivo reconstruction of connectivity patterns between nervous structures, to study the human analogues of the above‐mentioned direct cortico‐ and dento‐pallidal projections . These connections, likely paralleled by analogue cortico‐ and dento‐nigral pathways, may exert a converging influence of cerebral and neocerebellar cortex on the basal ganglia output nuclei.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, we used constrained spherical deconvolution (CSD)‐based tractography, a diffusion MRI‐based technique allowing in vivo reconstruction of connectivity patterns between nervous structures, to study the human analogues of the above‐mentioned direct cortico‐ and dento‐pallidal projections . These connections, likely paralleled by analogue cortico‐ and dento‐nigral pathways, may exert a converging influence of cerebral and neocerebellar cortex on the basal ganglia output nuclei.…”
mentioning
confidence: 99%
“…13,14 This scenario has been widely expanded since anatomical studies using retrograde virus tracing demonstrated bidirectional subcortical connections between cerebellum and basal ganglia. 15,16 More recently, we used constrained spherical deconvolution (CSD)-based tractography, a diffusion MRI-based technique allowing in vivo reconstruction of connectivity patterns between nervous structures, [17][18][19][20][21] to study the human analogues of the above-mentioned direct cortico- 22 and dento-pallidal projections. 23 These connections, likely paralleled by analogue cortico- 24 and dento-nigral 23,25 pathways, may exert a converging influence of cerebral and neocerebellar cortex on the basal ganglia output nuclei.…”
mentioning
confidence: 99%
“…In a recent review about 929 cases of zygomycosis, survival was 3% (8 of 241 patients) for cases that were not treated, 61% (324 of 532) for cases treated with amphotericin B deoxycholate, 57% (51 of 90) for cases treated with surgery alone, and 70% (328 of 470) for cases treated with antifungal therapy and surgery …”
Section: Discussionmentioning
confidence: 99%
“…The largely subcortical composition of the olfactory system, with many loci at the air-tissue interface, has presented a serious challenge to olfactory network identification, especially for unguided, whole-brain rs-fMRI connectivity analysis. However, important insights into the olfactory network have been gained by targeting olfactory regions of interest (ROIs) (Plailly et al, 2008;Krusemark and Li, 2012;Krusemark et al, 2013;Sunwoo et al, 2015;Kollndorfer et al, 2015;Novak et al, 2015;Karunanayaka et al, 2017;Milardi et al, 2017;Fjaeldstad et al, 2017;Cecchetto et al, 2019), especially in combination with network-science analysis (Meunier et al, 2014;Royet et al, 2011;Ripp et al, 2018;Zhou et al, 2019). The olfactory ROIs are fairly reliably identified, but inconsistencies in network composition and connections also abound in this literature (Fjaeldstad et al, 2017;Cecchetto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%